P3.224 Effect of Herpes Simplex Virus Type 2 (HSV-2) Infection on Progression of HIV Infection Among Female Sex Workers in Burkina Faso. (13th July 2013) - Traore, I T; Konate, I; Meda, N; Bazie, W; Hema, M N; Kabore, A; Kania, D; Mayaud, P; Perre, P Van De; Nagot, N
Abstract : Background: The effect of HSV-2 on the natural history of HIV-1 remains unclear. Although trials have shown a modest but significant impact of HSV-2 suppression on HIV-1 disease progression, the sub-optimal antiviral efficacy of aciclovir and its potential antiretroviral effect have limited our ability to measure the true effect of HSV-2 on HIV-1 disease progression. This study aimed to assess the effect of untreated HSV-2 infection on the time to ART. Methods: From December 2003 to February 2012, HIV-1 infected female sex workers were enrolled in a prospective open cohort in Burkina Faso. At each 3-month follow-up visits, CD4 count and HIV-1 plasma viral load were done. Participants were offered care including ART and psychological support. Participants not on ART and having at least 350 CD4 cells/µl at enrolment (the current CD4 count threshold for ART initiation) were included in this analysis, which was censored at 36 months of follow-up when the assumption of proportional hazard was no longer met. Results: Overall, 164 co-infected women and 20 HIV-1 mono-infected women were enrolled in this study. At enrollment, the only difference between the two groups was a younger age of HIV-1 mono-infected women (median age 24 versus 31 years, p < 0.001). In linear mixed models, the age-adjusted mean CD4 count at baseline (intercept) was significantly lower among HSV-2 positive women (–211 cell/µL, p < 0.001), but no difference in baseline CD4-adjusted plasma viral load was observed. During follow-up, 3 out 20 HIV-1 mono-infected women initiated ART versus 52 out of 164 HSV-2 co-infected women. After adjustment for baseline CD4 count and age, HSV-2 infected women were still much more likely to initiate ART over 36 months (HR = 4.6, CI 95%: 1.04–20.5, p = 0.04). Conclusion: HIV-1 disease progression, as assessed by time to ART eligibility, was much accelerated for women co-infected with HSV-2.